Myrmecofauna (Hymenoptera: Formicidae) present in vineyards infested with Eurhizococcus brasiliensis (Hemiptera: Margarodidae) in southern Brazil - Nondillo, Aline; Arioli, Cristiano Joao; Wild, Alexander; Bueno, Odair Correa [UNESP]; Botton, Marcos (Florida Entomological Soc, 2017)
Eurhizococcus brasiliensis (Wille) (Hemiptera: Margarodidae) is among the principal pests of Brazilian vineyards. Establishment and spread of this species in vineyards are associated with ants (Hymenoptera: Formicidae). This study determined the diversity of the ant fauna in E. brasiliensis infested vineyards in Rio Grande do Sul and Santa Catarina, the main grape-producing states in Brazil. Underground pitfall traps baited with a honey-water solution and sardines were used to sample ants in the spring-summer and fall-winter periods. Twenty-eight species of ants were identified in Rio Grande do Sul and 15 in Santa Catarina. Linepithema micans (Forel) (Hymenoptera: Formicidae) was the most frequent and abundant species collected in vineyards in both states. Control strategies for ants associated with the spread of E. brasiliensis should focus on L. micans in vineyards.
Keywords: survey; ant; soil scale; Linepithema micans